Operating Room Nurses' Understanding of Their Roles and Responsibilities for Patient Care and Safety Measures in Intraoperative Practice - Bisma Chellam Singh RN, BSN, MSN; Judie Arulappan MSc (N) (SAGE Publishing, 2023)
Introduction Surgical care has been a vital part of healthcare services worldwide. Several patient safety measures have been adopted universally in the operating room (OR) before, during, and following surgical procedures. Despite this, errors or near misses still occur. Nurses in the OR have a pivotal role in the identification of factors that may impact patient safety and quality of care. Therefore, exploring the OR nurses' understanding of their roles and responsibilities for patient care and safety in the intraoperative practice, which could lead to optimal patient safety, is essential. Objective This study explored the understanding of OR nurses regarding their roles and responsibilities for patient care and safety measures in the intraoperative practice. Methods The study was conducted in one of the tertiary care hospitals in the United Arab Emirates. Qualitative, descriptive, exploratory research design was utilized. The data were collected using semi-structured face to face interviews. Purposive sampling included eight nurses. Data analysis was performed following Colaizzi's seven-step strategy. Results Seven emerging themes were identified. The main themes are: patient safety, preoperative preparation, standardization of practice, time management, staffing appropriateness, staff education and communication, and support to the patient in the OR. Conclusion OR nurse leaders may take into consideration the current findings as a reference for quality improvement projects in the hospital, considering the specific characteristics of each local setting. Although the participants consider that the environment is safe and the quality of care is high in the study setting, there is still room for improvement on workflows and processes. OR workflow should be improved especially by addressing the potential patient safety issues.